PERBAIKAN KUALITAS MOLD PROSES INJECTION MOLDING PADA PT GIKEN PRECISION INDONESIA - Andika Nurhadi, Dwimas; Anggia Arista (LPPM Universitas Putera Batam, 2025)
PT Giken Precision Indonesia is a manufacturing company specializing in plastic molding products, located in Batam and established in 1991. Based on field observations, frequent mold damage in injection molding machines has resulted in defects in the wing eater product. This issue occurs due to the loosening of mold pins within the upper and lower plates of the mold. The total defective products for wing eater in one year reached 6.73%, exceeding the company’s tolerance limit of 5% annually. This study aims to improve the quality of injection molding molds in the wing eater production process and determine the appropriate mold design to enhance the injection molding process quality. The methods used in this study are Design for Manufacturing and Assembly (DFMA) and Defects Per Million Opportunities (DPMO). The results show that after designing an ejector set with upper plate and lower plate dimensions of 500 mm in length and 338 mm in width, the ejector pins were redesigned with two dimensional variations: a base diameter of 5 mm and a tip diameter of 4 mm. The percentage of defective products significantly decreased from 7.19% in January 2023 to 2.06% in February 2024. The Sigma level improved from 3.82 (10,170 DPMO) to 4.25 (2,980 DPMO), indicating a 70.7% reduction in defects. Thus, the mold quality can be improved.